Stream bank erosion as a source of sediment within New Zealand catchments - Andrew O. Hughes; Manawa K. Huirama; Philip N. Owens; Ellen L. Petticrew (New Zealand Journal of Marine and Freshwater Research, 2022)
Stream bank erosion has been anecdotally identified as an important source of sediment in New Zealand catchments, however, there have been few attempts to quantify its contribution. Here we use a radionuclide‐based sediment tracing approach to determine the relative contribution of stream bank‐ and hillslope‐derived sediment within three catchments in the upper North Island of New Zealand. Both lithogenic (radium‐226 and radium‐228) and fallout radionuclides (caesium‐137 and excess lead‐210) were used to differentiate sediment derived from stream bank and hillslope sources. The relative contribution of stream banks and hillslopes to fluvially transported suspended sediment were predicted using a mixing model approach. Our results indicate that both fallout and lithogenic radionuclides provide good source differentiation. We demonstrate that stream bank erosion can contribute very high proportions of sediment within New Zealand catchments. We used independent assessments of bank erosion from each of the study catchments to support the sediment source fingerprinting results. Further work is required to determine the spatial and temporal variability of the contribution of sediment from stream banks. Information on the importance of different sediment sources is needed to target limited catchment rehabilitation resources where they will have the most impact.